Pretreatment with nicotinamide mononucleotide increases the effect of ischaemic postconditioning on cardioprotection and mitochondrial function following ex vivo myocardial reperfusion injury in aged rats. (9th February 2022) - Rajabi, Mojgan; Vafaee, Manouchehr S.; Hosseini, Leila; Badalzadeh, Reza
Abstract: The present study aims to evaluate the combined effect of ischaemic postconditioning (IPostC) and nicotinamide mononucleotide (NMN) on cardioprotection and mitochondrial function in aged rats subjected to myocardial ischaemia–reperfusion (IR) injury. Sixty aged Wistar rats were randomly divided into five groups ( n  = 12), including sham, control, NMN, IPostC, and NMN + IPostC. Regional ischaemia was induced by 30‐min occlusion of the left anterior descending coronary artery (LAD) followed by 60‐min reperfusion. IPostC was applied at the onset of reperfusion, by six cycles of 10‐s reperfusion/ischaemia. NMN (100 mg/kg) was intraperitoneally injected every other day for 28 days before IR. Myocardial haemodynamics and infarct size (IS) were measured, and the left ventricles samples were harvested to assess cardiac mitochondrial function. The results showed that all treatments reduced lactate dehydrogenase release compared to those of the control group. IPostC alone failed to reduce IS and myocardial function. However, NMN and combined therapy could significantly improve myocardial function and decrease the IS compared to the control animals. Moreover, the effects of combined therapy on the decrease of IS, mitochondrial reactive oxygen species (ROS), and improvement of mitochondrial membrane potential (MMP) were greater than those of stand‐alone treatments. These results demonstrated that cardioprotection by combined therapy with NMN + IPostC was superior to individual treatments, and pretreatment of aged rats with NMN was able to correct the failure of IPostC in protecting the hearts of aged rats against IR injury.